Preference for Solitude and Mobile Phone Addiction Among Chinese College Students: The Mediating Role of Psychological Distress and Moderating Role of Mindfulness - Chen, Wan-Yi; Yan, Lei; Yuan, Yi-Ren; Zhu, Xiao-Wei; Zhang, Yan-Hong; Lian, Shuai-Lei (Frontiers in Psychology, 2021)
Background: With the increasing incidence of mobile phone addiction, the potential risk factors of mobile phone addiction have attracted more and more researchers’ attention. Although various personality trait factors have been proven to be significant predictors of mobile phone addiction, limited attention has been paid to preference for solitude. Considering the adverse impacts of preference for solitude in the context of collectivistic societies and its possible negative effect on mobile phone addiction, this study was designed to examine the relationship between preference for solitude and mobile phone addiction, and to test the mediating role of psychological distress and the moderating role of mindfulness in this relationship. Methods: Data were collected through convenience sampling from a comprehensive university in China. A total of 927 Chinese college students (371 males, 556 females), aged from 16 to 24 (Mage = 19.89 years, SD = 1.22), participated in this study. Their preference for solitude, psychological distress, mindfulness, and mobile phone addiction were measured using well-validated self-report questionnaires. Result: Correlational analyses, sobel test, SPSS macro PROCESS (Model 8) and simple slopes analyses were used for major data analysis. Results showed that preference for solitude was significantly and positively associated with mobile phone addiction, and this link could be mediated by psychological distress. Moreover, the indirect effect of psychological distress in this link was moderated by mindfulness, with this effect being stronger for college students with lower levels of mindfulness. However, mindfulness can not moderate the direct relation between preference for solitude and mobile phone addiction. Conclusions: The present study broadened our knowledge of how and when (or for whom) preference for solitude is related to mobile phone addiction. Education professionals and parents should pay special attention to the psychological distress and mobile phone addiction of college students with high levels of preference for solitude, particularly for those with lower levels of mindfulness.